NUTRITIONAL STATUS IN CHILDREN WITH CANCER: COMPARISON OF DEUTERIUM OXIDE DILUTION WITH BIOELECTRIC IMPEDANCE ANALYSIS AND ANTHROPOMETRY - Estela Beatriz Behling; José Simon Camelo Júnior; Eduardo Ferriolli; Karina Pfrimer; Jacqueline Pontes Monteiro (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To explore changes in the nutritional status of pediatric cancer patients before and after chemotherapy and evaluate the correlation between deuterium oxide dilution, bioelectric impedance analysis, and anthropometry for assessment of body composition. Methods: This study included 14 children (aged 5.6 to 13.6 years) and classified them as having hematologic or solid tumors. They had their body composition analyzed according to deuterium oxide, bioelectric impedance, and anthropometric measurements before the first chemotherapy cycle and after three and six months of therapy. Results: The patients in the hematologic tumor group had an increase in weight, height, body mass index, waist, hip, and arm circumference, subscapular skinfold thickness, and fat mass with the isotope dilution technique during chemotherapy. In the solid tumor group, the children showed a reduction in fat-free mass when assessed by bioimpedance analysis. We found a positive correlation between the triceps skinfold thickness and fat mass determined by bioimpedance analysis and deuterium oxide. The arm muscle circumference correlated with the fat-free mass estimated by bioimpedance analysis and deuterium oxide. Conclusions: Patients with hematologic tumors had an increase in body weight, height, and fat mass, which was not identified in the solid tumor group. The positive correlation between anthropometry (triceps skinfold thickness and arm muscle circumference), deuterium oxide dilution, and bioelectric impedance analysis shows the applicability of anthropometry in clinical practice.